SPECIES DIVERSITY OF SOIL FUNGI FROM A CORN PLANTATION AT ECHAGUE, PHILIPPINES - Rey Mark Gascon Tecson; Florenda C. Ballesteros - Temanel; James Kennard Sanz Jacob (SEAMEO BIOTROP, 2021)
Soil fungi are a critical component of agroecosystems and provide ecological services affecting food and bioproduct production. Awareness of the composition and distribution of local species is necessary to maximize the productivity and sustainability of agroecosystems. This study aimed at isolating fungi from soil samples collected from a corn plantation at Echague, Isabela, morphologically defining, characterizing, and determining the diversity of fungal isolate species. Soil samples from five (5) different sampling units were collected, and microbiological techniques were used to isolate the fungi. Identification was performed by morphological characterization of fungal isolates guided by taxonomic keys and textbooks. Fungal diversity was assessed using Simpson's indices of diversity. Sixteen (16) fungal isolates were found; 12 were known and four (4) were unidentified. Ten (10) species belonged to the Ascomycota group, and two (2) belonged to the Zygomycota class. Aspergillus species dominated the region among all species isolated and established. Aspergillus fumigatus and Aspergillus flavus were densely populated and well distributed. A potent biocontrol agent was also identified, namely Trichoderma harzianum and Trichoderma viride. The Mucor sp. and Rhizopus stolonifer (Zygomycota fungi) were also identified.